Determination of Destruction Levels Caused by Earthquakes Using Grip RADIUS 99 Program - Abd Al – Mageed, Tahrer Adnan; Ismail Mahmood, Maath; Hamoody Saloom, Baker; Mageed Hmeed, Dalya; Jassim Mohamed, Hamad (Iraqi Journal of Science, 2023)
The most universal and basic damages caused by an earthquakes are buildings damage and human casualties. A simplified method, the RADIUS 99 Tool is used to calculate seismic intensity (shaking) distribution, buildings damage, number of casualties and lifelines damage, due to assumed earthquake scenario. In this study, Al - Kadhmiya sector in Baghdad city was chosen for assessing seismic risk, for this purpose, this area was divided into mesh of 1*1 km2 cell size, and a scenario of (Manjil) earthquake (that struck Iran in 1990) was utilized with following earthquake magnitudes (5 and 7), with epicenter distance (3, 10 and 100 km), and depths (2 and 5 km). It was found that, the best soil types for constructions are those with medium and hard soils, where they can resist the earthquake. The areas with soft soils should be avoided when we want to choose the sites to build the life saving establishments and general public buildings like schools and hospitals, in addition, the seismic building code should be followed for structures to be built on soft soils areas.